2018
DOI: 10.1016/j.jsps.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between satisfaction with and adherence to warfarin therapy on the control of international normalized ratio: A hospital-based study in Saudi Arabia

Abstract: Substantial efforts are needed to improve patient satisfaction and adherence to treatment through different strategies in order to achieve the target therapeutic goal for warfarin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…It was observed that the males had greater satisfaction with their anticoagulation treatment compared to females and education did not correlate significantly with overall DASS score and its subscale. Satisfaction with anticoagulation and being a male in our study is similar to a survey by Balkhi who reported that male participants and those with higher secondary education were more satisfied with their anticoagulation therapy (Balkhi et al, 2018). Our findings are similar to the Turkish study which reported no relation between overall DASS score and its subscales with education (Yıldırım and Temel 2014).…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that the males had greater satisfaction with their anticoagulation treatment compared to females and education did not correlate significantly with overall DASS score and its subscale. Satisfaction with anticoagulation and being a male in our study is similar to a survey by Balkhi who reported that male participants and those with higher secondary education were more satisfied with their anticoagulation therapy (Balkhi et al, 2018). Our findings are similar to the Turkish study which reported no relation between overall DASS score and its subscales with education (Yıldırım and Temel 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Assessing the QoL is important in order to improve the quality of care for anticoagulated patients. It has been shown that satisfaction correlates with adherence and INR control40,41 and that, in turn, the TTR correlates with thromboembolic and bleeding complications 42. By identifying limitations and hassles associated with VKA treatment, health care professionals can provide specific educational interventions to improve the burden associated with this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…21 Treatment satisfaction, which includes the perceived burden and benefit that a patient attributes to their treatment, has been associated with better treatment adherence among older patients with AF. 22,23 Patient satisfaction of AF treatment is therefore central in achieving the target therapeutic goal for treatment.…”
mentioning
confidence: 99%